2011
DOI: 10.2214/ajr.10.4990
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Normalized Reference Values of Heart and Great Vessel Dimensions in Cardiac CT Angiography

Abstract: Cardiac CTA measurements of the left cardiac chambers, thoracic aorta, and pulmonary arteries were established for a population without CAD or its risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 11 publications
1
39
1
Order By: Relevance
“…The increase in CO is mediated via increased IVC flow, with the SVC flow staying relatively constant. The values and trends of EF are consistent with previous literature reports [30,44,45]. The resulting atrial pressures are similar to values reported by Leupker et al, and remain relatively steady at different MET levels with some increases at high MET levels as clinically observed during continuous exercise [36].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The increase in CO is mediated via increased IVC flow, with the SVC flow staying relatively constant. The values and trends of EF are consistent with previous literature reports [30,44,45]. The resulting atrial pressures are similar to values reported by Leupker et al, and remain relatively steady at different MET levels with some increases at high MET levels as clinically observed during continuous exercise [36].…”
supporting
confidence: 90%
“…Based on literature data of end diastolic and systolic volume (EDV and ESV) measurements in humans [30,44,45], and clinical knowledge of ejection fractions (EF) that represent typical Fontan patients, we define an equation for V svo that results in realistic pressure-volume loops 081007-4 / Vol. 136, AUGUST 2014…”
Section: à2mentioning
confidence: 99%
“…However, it appears the gender differences could largely be accounted for by differences in the BSA between men and women [20,42] for the main PA size, with the exception of the right PA. Similarly, gender differences in the size of the aorta could also be explained by adjusting for the BSA, but notably not the ascending aorta [42].…”
Section: What Is the Normal Reference Value?mentioning
confidence: 99%
“…Such noninvasive approach can reduce patient's risk and allow earlier PH diagnosis. Though management decisions strongly depends on comparison of measured parameters with normal values, little has been published in reference to normal CT limits of thoracic aorta and pulmonary trunk (PT) parameters, as well as their association to variable factors (Wolak et al;Lin et al, 2008;Nevsky et al, 2011).…”
Section: Introductionmentioning
confidence: 99%